The settlement of anthropogenic water-bodies of Silesia by Ferrissia clessiniana (Jickeli) - Małgorzata Strzelec (Malacologica Bohemoslovaca, 2005)
In last two decades Ferrissia clessiniana (Jickeli, 1802) was observed in anthropogenic water-bodies in Silesia (Southern Poland). Formerly this species was found only in Western and Central Poland. In Silesia it settles the subsidence ponds, sand- and gravel-pits and dam reservoirs, where lives mostly in the rush belts. In the absence of vegetation F. clessiniana inhabits the stones, covered with periphyton layer, and the remains of decayed water-plants and leaves of waterside trees. Never forms the dense populations.